A 2019 Social Accounting Matrix for Benin with detailed representation of agriculture and food processing sectors - Kinkpe, A. Thierry,Luckmann, Jonas Jens,Grethe, Harald,Siddig, Khalid (Department of Agricultural Economics, Faculty of Life Sciences, Humboldt-Universität zu Berlin, 2022)
This paper presents a detailed 2019 Social Accounting Matrix (SAM) for Benin as a basis for policy analysis with a focus on agriculture, food processing and energy generation from byproducts. It is based on official statistics collected from national and international institutions (national statistical office, ministry of agriculture and related research institutions, central bank, World Bank, United Nations) and complemented with data collected from stakeholders within the domestic processing sector and NGOs supporting agriculture and food processing. A top-down approach was followed starting with national accounts data to build a consistent macro-SAM. The values in the macro-SAM were used as macro-totals while disaggregating a prior micro-SAM (with minor imbalances), which is estimated using the Cross-Entropy method. The micro-SAM contains 127 accounts: 47 activities (19 agricultural, 12 food processing, 9 non-food industries, construction and 6 service sectors); 51 commodities (21 agricultural, 13 food processing, 10 non-food industries, construction and 6 service commodities); 3 margins; 4 production factors; 10 household groups (rural and urban income quintiles), the government as well as 6 tax accounts; enterprises, 2 savings/investment accounts (private and public) and 2 foreign accounts (Nigeria and the rest of the world). The estimated SAM reflects total GDP at factor cost at FCFA 7.7 trillion (about US 13.1 billions). Services, agriculture, construction, non-food industry and food industry contribute 60.3%, 29.1%, 5.2%, 2.7% and 2.6% respectively to GDP. Labour and land are the most important income sources for low income households while capital and labour provide most of the income of high-income households.
10419/253338
Keywords: Graue Literatur; SAM; agriculture; food processing; green-energy; Computable General Equilibrium (CGE) model; developing country